Impact of cyclooxygenase-2 over-expression on theprognosis of breast cancer patients - (:unkn) unknown (My University, 2016)
Amaç: Bu çalışmanın amacı, COX-2 ekspresyonunun meme kanseri sağkalımı üzerine etkilerini değerlendirmektir Gereç ve Yöntemler: Yeterli lokorejyonel ve sistemik tedavi almış olan non-metastatik invaziv meme kanseri hastaları değerlendirildi. Hastaların demografik, klinik, patolojik, tedavi ve sağkalım bilgileri hastane kayıtlarından temin edildi. Tümörün COX-2, östrojen/progesteron reseptör (ER/PR), HER-2/neu ekspresyonu ve Ki67 indeksi immünohistokimyasal olarak değerlendirildi. Birincil çıkarım olarak, genel sağkalım (GS), hastalıksız sağkalım (HS) ve meme kanserine özgü sağkalım (MKÖS) açısından COX-2 negatif ve pozitif hastalar karşılaştırıldı. İkincil çıkarım olarak sağkalıma etki eden bağımsız prognostik faktörler değerlendirildi. Ayrıca COX-2 ekspresyonunun meme kanserinin konvansiyonel prognostik faktörleri ve prediktif faktörleri ile bağlantısı incelendi.Bulgular: Kasım 2004 ile Aralık 2013 tarihleri arasında yeterli meme kanseri tedavisi almış olan 217 hasta çalışmaya alındı. Ortalama takip süresi 37 aydı . Seksen bir (%37) hasta COX-2 pozitifti. GS, HS ve MKÖS, COX-2 pozitif ve negatif hastalarda benzerdi. Ki67 indeksi ve yaş COX-2 ile anlamlı olarak bağlantılıydı (r=-0,116; p=0,02; r=0,159; p=0,02). GS için tek bağımsız prediktör PR ekspresyonu; HS için bağımsız prediktörler tümör boyutu ve moleküler alt grup sınıflandırması; MKÖS için de yine tek prediktör faktör PR ekspresyonu olarak bulundu.Sonuç: COX-2 ekspresyonu, meme kanserinin bağımsız prediktif ve prognostik faktörleri içinde sadece Ki67 indeksi ve yaş ile ilişkilidir.

Objective: The aim of this present study was to assess the impact of COX-2 over-expression on breast cancer survival. Material and Methods: Non-metastatic invasive breast cancer patients who received adequate loco-regional and systemic treatments were evaluated. Patients' demographic, clinical, pathologic, and treatment-related and survival data were retrieved from their hospital files. COX-2, estrogen/progesterone receptor (ER/PR), HER-2/neu expression and Ki67 index of the tumors were determined immunohistochemically. As the primary objective, COX-2 positive and negative patients were compared in terms of overall (OS), disease-free (DFS) and breast cancer-specific survival (BCSS). Secondary objectives were to assess the independent prognostic factors for survival. In addition, the correlation of COX-2 expression with conventional prognostic and predictive factors of breast cancer was assessed.Results: Two hundred and seventeen patients who underwent adequate breast cancer treatment between November 2004 and December 2013 were included in the study. The median follow-up was 37 months . Eighty-one (37%) patients were COX-2 positive. OS, DFS, and BCSS were similar in COX-2 positive and negative patients. Ki67 index and age were significantly correlated with COX-2 expression (r=-0.116; p=0.02; r=0.159; p=0.02). PR expression was found to be the only independent factor for predicting OS, tumor size and molecular subtype classification were found to be the only independent factors for predicting DFS, and PR expression was found to be the only independent factor for predicting BCSS.Conclusion: Among the independent predictive and prognostic factors of breast cancer, COX-2 over-expression was only correlated with Ki67 index and age.
Meme kanserinde siklooksijenaz-2 ekspresyonunun prognoza etkisi
Keywords: Cerrahi